ASSESSEMENT OF MYOCARDIAL MECHANOENERGETIC EFFICIENCY IN PATIENTS WITH PRIMARY ALDOSTERONISM. (June 2018) - Bertacchini, F.; Paini, A.; Salvetti, M.; Stassaldi, D.; Maruelli, G.; Rosei, C. Agabiti; Aggiusti, C.; Riviera, M.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: Available data indicate that patients with primary aldosteronism (PA) have an increased risk of cardiovascular (CV) events; furthermore, CV risk seems to be, at least in part, independent of blood pressure (BP) elevation. Previous studies have shown that patients with PA have a greater prevalence of left ventricular (LV) hypertrophy, which might contribute to the increase in CV risk. Recently, a non-invasive approach for the estimation of LV mechanical efficiency through the calculation of the ratio between stroke work (SW) and heart rate (HR)–pressure product has been proposed by de Simone and coworkers. This index, which expresses the amount of blood pumped in a single beat in 1 second by the heart, may be easily obtained by echocardiography. Design and method: The aim of our study was to evaluate the determinants of myocardial mechanoenergetic efficiency index (MEEi), calculated as SV/HR and indexed to LV mass (MEEi = MEE/LVM) in a large group of patients with primary aldosteronism and in a control group of essential hypertensives (EH). PA was diagnosed in the presence of a positive aldosterone to renin ratio (>30) and post saline aldosterone > 100ng/ml). Ninety-nine patients with PA were compared with 99 EH patients matched for age and BP values. Results: No differences between groups were observed for age, gender, BMI, BP values, glucose, lipid profile and renal function. LV mass index was greater in PA vs EH (101 ± 34 vs 84 ± 20, gr/m2, p < 0, 05); also relative wall thickness was greater in PA vs EH (0.36 ± 0.1 vs 0.32 ± 0.4, p < 0, 05). Ejection fraction was not different between groups, while endocardial and midwall fractional shortening were lower in PA vs EH (40 ± 7 vs 43 ± 6, and 18 ± 3 vs 21 ± 2 both p < 0, 05). MEEI was lower in PA vs EH (0.44 ± 0.14 vs 0.52 ± 0.10, p < 0, 05). A negative correlation was observed between MEEI and aldosterone levels (r = −0.20, p < 0.05). Conclusions: In patients with primary aldosteronism MEEI is lower as compared to EH. These findings may contribute to explain the increased risk of CV events in patients with PA.